ASSESSING THE IMPACT OF INFLATION, UNEMPLOYMENT ON POVERTY AND HUMAN DEVELOPMENT INDEX IN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
This study carefully assessed the impact of inflation and unemployment on poverty and the human development index in Nigeria using an annual dataset from 1991 to 2023. A vector autoregression (VAR) model was used for data analysis. The findings of the analysis indicate that the unit root test for the variables at first difference was stationary at the 5% critical value, the Johansen cointegration test for both trace and maximum eigenvalue had one cointegrating equation, meaning that there is a short- and long-term equilibrium relationship among the variables, while the optimal lag selection criteria showed a lag length of order one. Hence, these results met the requirements for using vector error correction (VEC) model estimation, given that the CUSUM test also indicates the model residual parameters' stability. Meanwhile, the impulse response functions revealed that a unit shock to inflation increases unemployment and poverty, as well as reduces government spending on human development through education and health. Also, the forecast variance decomposition showed the influence of the variability of inflation among variables, demonstrating its negative impact on various facets of the economy, leading to high rates of unemployment and poverty as it hampers human development. In view of this, the empirical study submits that researchers, policymakers, and development practitioners should design effective policies and programs that will help in reducing the effect of inflation and unemployment rates on poverty and the human development index through poverty reduction intervention programs aimed at fostering sustainable economic growth and human development in Nigeria.
Keywords: VAR; Inflation; Unemployment; Poverty; Human Development Index